A Biomimetic In Vitro Model of the Kidney Filtration Barrier Using Tissue‐Derived Glomerular Basement Membrane (Adv. Healthcare Mater. 16/2021). Issue 16 (17th August 2021) - Wang, Dan; Sant, Snehal; Ferrell, Nicholas
Abstract : Glomerular Basement Membranes In article number 2002275 by Nicholas Ferrell and co‐workers, a biomimetic tissue culture model of the kidney filtration barrier is developed to evaluate molecular transport. The in vitro filtration barrier model employs kidney‐derived glomerular basement membrane to replicate the in vivo microenvironment. The filtration barrier model exhibits molecular selectivity and damage to the basement membrane increases molecular permeability.